Measuring Financial Access : 10 Years of the IMF Financial Access Survey - Espinosa-Vega, Marco (Departmental Papers; Departmental Paper ;, 2020)
This departmental paper marks the 10th anniversary of the IMF Financial Access Survey (FAS). It offers a retrospective of the FAS database, along with some reflections as to its future directions. Since its 2009 launch, the FAS has provided granular data on access to and use of financial services. It is a supply-side database with annual global coverage based on data sourced directly from financial service providers-aimed at supporting policymakers to target and evaluate financial inclusion policies. Its data collection has kept pace with financial innovation, such as the rise of mobile money and growing demand for gender-disaggregated data-and the FAS must continue to evolve.